Recurrent SLCO1B1 and SLCO1B3 mutations identified in three patients with Rotor syndrome - Chenyu Zhao; Chenyu Zhao; Hui Huang (Frontiers in Medicine)
BackgroundRotor syndrome is a rare genetic disease inherited in an autosomal digenic recessive manner. It is caused by pathogenic mutations in both SLCO1B1 and SLCO1B3 genes, and characterized by predominantly conjugated hyperbilirubinemia.MethodsThree Chinese patients clinically diagnosed with Rotor syndrome were included. Mutations in SLCO1B1/3 genes were identified using whole-exome sequencing.ResultsThey all carried the same homozygous c.1738C>T mutation in SLCO1B1 and the c.481+22insLINE variant in SLCO1B3.ConclusionThis study established a genetic diagnosis for the three patients and contributed to finding hotspot mutations in Rotor syndrome.